Use of mycophenolate mofetil and a calcineurin inhibitor in allogeneic hematopoietic stem-cell transplantation from HLA-matched siblings or unrelated volunteer donors: Japanese multicenter phase II trials - Nakane, Takahiko; Nakamae, Hirohisa; Yamaguchi, Takuhiro; Kurosawa, Saiko; Okamura, Atsuo; Hidaka, Michihiro; Fuji, Shigeo; Kohno, Akio; Saito, Takeshi; Aoyama, Yasutaka; Hatanaka, Kazuo; Katayama, Yoshio; et al. (International journal of hematology, 2017)
To test the feasibility of mycophenolate mofetil (MMF) for graft-versus-host disease (GVHD) prophylaxis in Japanese patients, we conducted two multicenter prospective phase II trials of allogeneic hematopoietic stem-cell transplantation (HSCT) from HLA-matched related donors (MRD group) with MMF and cyclosporine or HLA 7–8/8 allele-matched unrelated bone-marrow donors (URD group) with MMF and tacrolimus. The cumulative incidences of grade II–IV acute GVHD on day 100, which was the primary endpoint in these trials, were 45.0% (90% CI 25.8–62.5) and 25.8% (90% CI 13.9–39.5) in the MRD ( n = 20) and URD ( n = 31) groups, respectively. The rates of 3-year overall survival and non-relapse mortality were 80.0 and 15.0% in the MRD group and 74.2 and 6.5% in the URD group, respectively. GVHD prophylaxis with MMF may lead to a lower incidence of severe mucositis and faster neutrophil engraftment compared to that with methotrexate. A pharmacokinetics study of mycophenolic acid (MPA) showed that a relatively higher plasma concentration of MPA was associated with a lower incidence of acute GVHD. In conclusion, the results of these studies suggest that GVHD prophylaxis with MMF may be useful as an alternative in Japanese patients who may benefit from faster engraftment or less severe mucositis after allogeneic HSCT.